Monitoring the Opinion of the Crowd: Psychological Mechanisms Underlying Public Opinion Perceptions on Social Media. Issue 3 (3rd July 2017) - Neubaum, German; Krämer, Nicole C.
Abstract : Social media technologies offer several features that allow users to monitor other people's opinions on public issues. Initial research showed that user-generated content can shape recipients' perceptions of the majority opinion on societal problems. Still, it remains largely unexplored under which circumstances people gauge other users' opinions through social media and whether perceived opinion climates affect people's opinions and communication behavior in these environments. Results of a two-session experiment revealed that people's fear of isolation sharpens their attention toward user-generated comments on Facebook which, in turn, affect recipients' public opinion perceptions. The latter influenced subjects' opinions and their willingness to participate in social media discussions. These findings are discussed in light of the spiral of silence theory and the social projection hypothesis.